21st century guitar evolutions and augmentations - (Guitarist) McGrath, John; (Guitarist) Perks, Rich (Bloomsbury Academic, 2023)
examines the diverse physical manifestations of the guitar which have emerged in response to the needs of the modern performer and explores the creative possibilities these new forms afford"--